Myocardial Ischemia During Mental Stress: Role of Coronary Artery Disease Burden and Vasomotion. Issue 5 (21st October 2013) - Ramadan, Ronnie; Sheps, David; Esteves, Fabio; Maziar Zafari, A.; Douglas Bremner, J.; Vaccarino, Viola; Quyyumi, Arshed A.
Abstract : Background: Mental stress–induced myocardial ischemia (MSIMI) is associated with adverse prognosis in patients with coronary artery disease (CAD), yet the mechanisms underlying this phenomenon remain unclear. We hypothesized that compared with exercise/pharmacological stress–induced myocardial ischemia (PSIMI) that is secondary to the atherosclerotic burden of CAD, MSIMI is primarily due to vasomotor changes. Methods and Results: Patients with angiographically documented CAD underwent 99m Tc‐sestamibi myocardial perfusion imaging at rest and following both mental and physical stress testing, performed on separate days. The severity and extent of CAD were quantified using the Gensini and Sullivan scores. Peripheral arterial tonometry (Itamar Inc) was used to assess the digital microvascular tone during mental stress as a ratio of pulse wave amplitude during speech compared with baseline. Measurements were made in a discovery sample (n=225) and verified in a replication sample (n=159). In the pooled (n=384) sample, CAD severity and extent scores were not significantly different between those with and without MSIMI, whereas they were greater in those with compared with those without PSIMI ( P <0.04 for all). The peripheral arterial tonometry ratio was lower in those with compared with those without MSIMI (0.55±0.36 versus 0.76±0.52, P =0.009). In a multivariable analysis, the peripheral arterial tonometry ratio was the only independent predictor of MSIMI ( P =0.009), whereas angiographic severity and extent of CAD independently predicted PSIMI. Conclusions: The degree of digital microvascular constriction, and not the angiographic burden of CAD, is associated with MSIMI. Varying causes of MSIMI compared with PSIMI may require different therapeutic interventions that require further study.